Spatial Analysis of Diarrhea Incidences, Environmental Influences, and Behavioral Factors in An Ecological Study - Adria, Baby Putri; Wulandari, Ririn Arminsih; Kurniasari, Fitri (Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Diarrhea is a global health problem that causes morbidity and death in all age groups. Among the cities in Indonesia, Depok has the second-highest incidence of diarrhea outbreaks. Although previous studies have shown the correlation between diarrhea and environmental and behavioral factors, the spatial analysis of these factors is still very limited. Therefore, in this study, we investigated the spatial analysis of the association between diarrhea incidence and environmental and behavioral factors using an ecological study. The secondary data from the Depok City Health Office were used in the analysis. Our results showed a significant relationship between proper drinking water coverage (p = 0.00; r = -0.289) and healthy latrine coverage (p = 0.02; r = -0.233) with the incidence of diarrhea. Meanwhile, household coverage of Clean and Healthy Behavior (Perilaku Hidup Bersih dan Sehat (PHBS)) and population density showed no significant association. Spatial analysis maps also revealed the distribution pattern of diarrhea in Depok City from 2013 to 2021, tending to be more common in areas with low coverage of adequate drinking water. The findings from this study will contribute to optimizing diarrhea control and prevention programs.